A randomized-control trial testing the impact of a multidisciplinary team response to older adult maltreatment. Issue 4 (20th October 2019) - DePrince, Anne P.; Hasche, Leslie K.; Olomi, Julie M.; Wright, Naomi M.; Labus, Jennifer
ABSTRACT: Forensic center multidisciplinary teams (MDTs) have emerged to address older adult maltreatment; however, little research is available on this approach. The current study employed a randomized-control design to test the impact of a victim-focused, forensic center MDT relative to usual care (UC) on older adult victim and criminal justice outcomes. Cases of abuse, neglect, and/or financial exploitation involving a perpetrator in a position of trust were randomly assigned to MDT or UC. Outcomes were assessed via interviews with older adult victims, system-based advocates' surveys, and administrative data. According to system-based advocates, MDT had a better prognosis, higher across-agency coordination, and more types of engaged services relative to UC. Administrative data indicated low rates of APS case openings and prosecution. Findings provide support for continued use of MDTs following older adult maltreatment and highlight difficulties engaging older adults given the complex social and material circumstances often related to maltreatment.